2018
DOI: 10.1007/s11060-018-2799-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the TWEAK receptor Fn14 in IDH1 wild-type and mutant gliomas

Abstract: The TNF receptor superfamily member Fn14 is overexpressed by many solid tumor types, including glioblastoma (GBM), the most common and lethal form of adult brain cancer. GBM is notable for a highly infiltrative growth pattern and several groups have reported that high Fn14 expression levels can increase tumor cell invasiveness. We reported previously that the mesenchymal and proneural GBM transcriptomic subtypes expressed the highest and lowest levels of Fn14 mRNA, respectively. Given the recent histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…IDH1 Arg132His (R132H) mutation can affect the proliferation of glioma cells, which is slower than the corresponding wild-type IDH1 cells ( 8 , 9 ). Clinical studies ( 10 , 11 ) have shown that mutations in IDH1 were found to be associated with younger age, secondary GBMs (grade IV tumors that arise from biopsy-proven lower-grade predecessors), and increased overall survival (OS) ( 12 ). Further studies ( 13 , 14 ) have revealed that IDH1/2 mutations as good prognostic markers are universally present in grade II and III glioma and secondary glioblastoma, and serve an important role in the occurrence, development and evolution of glioma ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…IDH1 Arg132His (R132H) mutation can affect the proliferation of glioma cells, which is slower than the corresponding wild-type IDH1 cells ( 8 , 9 ). Clinical studies ( 10 , 11 ) have shown that mutations in IDH1 were found to be associated with younger age, secondary GBMs (grade IV tumors that arise from biopsy-proven lower-grade predecessors), and increased overall survival (OS) ( 12 ). Further studies ( 13 , 14 ) have revealed that IDH1/2 mutations as good prognostic markers are universally present in grade II and III glioma and secondary glioblastoma, and serve an important role in the occurrence, development and evolution of glioma ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, TNFRSF12A was more highly expressed in IDH wild-type gliomas than gliomas with IDH mutations. One study reported that TNFRSF12A promoted the invasive phenotype of IDH1 wild-type gliomas, while IDH1-mutant gliomas exhibited low TNFRSF12A mRNA and protein levels compared with IDH1 wild-type gliomas (47).…”
Section: Discussionmentioning
confidence: 99%
“…PDGFB and SERPINE1 mRNA expression data corresponding to 10 normal brain and 548 GBM specimens were downloaded from the TCGA data portal (Level 3 data) (Cancer Genome Atlas Research Network, 2008) and analyzed as previously described (Hersh, Peng, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%